Characteristics of uterine bleeding associated with an oral contraceptive containing drospirenone in combination with estetrol: A multicenter observational study - Irina V. Kuznetsova; Liudmila V. Evsyukova (IP Berlin A.V., 2024)
Background. An unfavorable bleeding pattern is a common reason for refusing to continue hormonal contraception. Aim. To evaluate the characteristics of uterine bleeding when using a new combined oral contraceptive (COC) containing estetrol and drospirenone (Esteretta®). Materials and methods. A multicenter observational study included 1402 females aged 18-49 who received Esteretta® for 6 cycles. The frequency, duration, and severity of withdrawal bleeding, as well as the frequency of unpredictable bleeding, were assessed. Results. The rate of regular withdrawal bleeding was 100%. The proportion of women with heavy menstruation/withdrawal bleeding decreased from 29.6 to 10.07% (p0.0001). The duration of regular withdrawal bleeding was significantly reduced (p=0.008). The incidence of unpredictable bleeding during COC use decreased from 4.57 to 3.29% (p=0.05). Satisfactory cycle control was observed in 87.43% of women. 2.5% of participants refused to continue using COCs. Conclusion. Esteretta® provides a high rate of regular withdrawal bleeding and a low rate of unpredictable bleeding. Given the optimal safety profile, this drug may be the first choice for contraception in sexually active women who are not planning a pregnancy.